Vigor dan Viabilitas Kecambah Kacang Tanah (Arachis hypogaea L.) Keturunan Pertama (F1) Hasil Persilangan antara Varietas Nasional dengan Lokal Bima - Arief Rahman Hakim (Biocaster : Jurnal Kajian Biologi, 2022)
Peanut (Arachis hypogaea L.) is a legume crop and is one of the second highest yielding secondary crops after soybeans. Peanut production in Indonesia tends to fluctuate and is still not able to meet the needs of the community every year. To produce quality seeds, one of the ways that plant breeders do is by crossing. The cross in this study was a peanut cross between the national variety and the local Bima variety. The purpose of this study was to determine the vigor and viability of peanut sprouts from crosses between national and local varieties of Bima. This research is included in pure experimental research. The design used in this study was a completely randomized design. The data in the research that has been collected through observation and documentation methods are then analyzed using ANOVA One Way. Based on the results of the study, the data on viability parameters were obtained, namely: the highest percentage of germination was obtained by F1A seeds (Rhinoceros Variety x Local Bima) with a value of 86.66% while the lowest percentage of germination was F1C seeds (V. Kancil x Local Bima) with a value of 20%. For the parameter of germination speed, the F1 seed which had the highest seed germination speed was F1E (V. Pelanduk x Local Bima) with a value of 2.33/day while the lowest germination rate was F1C (V. Kancil x Local Bima) with a value of 0.58/day. From all research data, it was found that data from all parameters experienced significant variations or differences with P Value < 0.05 in each treatment.